The Role of Artificial Intelligence in Enhancing User Experience on OTT Platforms - Chahwala, Keshav; Shubham, Chavda; Zalariya, Nihal; Dhruv, Aryan; Rakesh Shah, Arya; Chauhan, Rahul; Maseleno, Andino (Greenation Research & Yayasan Global Resarch National, 2025)
This study investigates the impact of Artificial Intelligence (AI) on user experience and engagement with Over-the-Top (OTT) platforms, focusing on Ahmedabad, India. The research examines how AI-driven content personalization and predictive analytics influence user satisfaction and retention. Using a quantitative approach, data was collected from 101 respondents via a structured questionnaire and analyzed using SPSS software. Key findings reveal that AI-based content recommendations significantly enhance user satisfaction, with noticeable differences in engagement across age groups. Gender-based analysis shows a variance in time spent on platforms, though content preferences and response to recommendations remain consistent across genders. The study highlights the growing importance of AI in optimizing user experiences and driving engagement on OTT platforms. Future research can explore regional variations, ethical challenges, and evolving AI technologies in streaming services to further refine personalization strategies.